2009
DOI: 10.2740/jisdh.20.33
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of eating habits based on the transtheoretical model for healthy eating behavior among college students

Abstract: Recently high frequency of breakfast skipping and low intake of vegetable are common among adolescents and young adults in Japan. Based on the stages of change, which is a key concept of the transtheoretical model, this study aimed to investigate the actual situation and reveal the problems with regard to eating habits among college students and threw light on the intervention for sensible diet. Data was provided by the sample of 268 participants mean age 19.8 years, SD 1.28 .The results of the questionnaire s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the present study, majority of the participants were categorized as non-gender-typed personalities (i.e., androgynous and undifferentiated), which is consistent with a recent study in Japan ( 22 ). This may partly due to the recent changes in gender norms related to work and household tasks in Japan ( 24 ), and these traits are also seen in the United States. In the previous study, women’s BSRI masculine trait scores increased steadily over the 20-year period ( 13 , 26 ), and the other study showed the significant decrease of women’s femininity scores between 1993 and 2012 ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, majority of the participants were categorized as non-gender-typed personalities (i.e., androgynous and undifferentiated), which is consistent with a recent study in Japan ( 22 ). This may partly due to the recent changes in gender norms related to work and household tasks in Japan ( 24 ), and these traits are also seen in the United States. In the previous study, women’s BSRI masculine trait scores increased steadily over the 20-year period ( 13 , 26 ), and the other study showed the significant decrease of women’s femininity scores between 1993 and 2012 ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literacy about healthy eating was assessed with the healthy eating literacy (HEL) scale ( 23 ). The HEL consists of five items about food-related factors, and is validated with the transtheoretical model of healthy diet ( 24 ). The HEL is a content-specific version of the HL scale ( 25 ) for food-related information.…”
Section: Methodsmentioning
confidence: 99%
“…The transtheoretical model (TTM) developed by Prochaska et al reached Japan in the late 1990s [ 30 ]. Research reports of Japanese participants published since 2000 have shown that the higher the stage of behavior change (maintenance and implementation), the higher the breakfast consumption and the better the dietary balance [ 31 ]. There are research reports on exercise items and a scale for maintaining balanced decision-making (κ-coefficient 0.75) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%